Comparative Evaluation of Simplified Hydroponic Techniques for Vegetable Cultivation - AJAY JAYAKUMAR BINSHA K.T JESNA D. SILVA; Dr. Rema K.P (Guide) (Tavanur 2017 DEPARTMENT OF IRRIGATION AND DRAINAGE ENGINEERING)
Comparative Evaluation of Simplified Hydroponic Techniques for Vegetable Cultivation
Comparative Evaluation of Simplified Hydroponic Techniques for Vegetable Cultivation